The Routledge handbook of terrorism research - Schmid, Alex P. (Routledge handbooks, 2011)
Focuses on political terrorism. This handbook collects definitions, conceptual frameworks, paradigmatic formulations, and bibliographic sources for the community of researchers on the subject of terrorism. It is suitable for students of terrorism, political science and security studies, and policy makers and professionals in the security field.